2019
DOI: 10.5334/aogh.2515
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Noise and Heat Strain on the Work Ability Index (WAI) among Rubber Factory Workers

Abstract: Introduction: Assessing the work ability and factors affecting it is essential in developing strategies for preventing damages and managing risks. This study aimed to investigate the simultaneous effect of noise level and physiological strain as well as individual characteristics on the work ability. Method: The population in this cross-sectional study included workers of a rubber factory. The TES noise dosimeter was used to examine individual exposure and the electro p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…We have planned a further study to evaluate this possibility by analyzing, in addition to the WAI, levels of occupational stress, anxiety, and depression in male and female workers. In fact, the literature tells us that the WAI score is associated with occupational stress [ 43 , 44 , 45 , 46 ] and emotional factors [ 47 , 48 , 49 ]. The relationship between stress, psychiatric problems, and the WAI is complex and probably cyclical: according to the Stockholm County longitudinal study, after 4 years, compared to their colleagues, workers with a low WAI had an almost twice as high a rate of distress [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have planned a further study to evaluate this possibility by analyzing, in addition to the WAI, levels of occupational stress, anxiety, and depression in male and female workers. In fact, the literature tells us that the WAI score is associated with occupational stress [ 43 , 44 , 45 , 46 ] and emotional factors [ 47 , 48 , 49 ]. The relationship between stress, psychiatric problems, and the WAI is complex and probably cyclical: according to the Stockholm County longitudinal study, after 4 years, compared to their colleagues, workers with a low WAI had an almost twice as high a rate of distress [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of dimension values results in a total WAI score that can range from 7 (unable to work) to 49 (full work ability). Based on this score, an individual is classified into standard work ability categories of excellent (WAI [44][45][46][47][48][49], good (WAI 37-43), moderate (WAI [28][29][30][31][32][33][34][35][36], and poor (WAI ~27).…”
Section: Introductionmentioning
confidence: 99%
“…We have planned a further study to evaluate this possibility by analyzing, in addition to the WAI, levels of occupational stress, anxiety and depression in male and female workers. In fact, the literature tells us that the WAI score is associated with occupational stress [39][40][41][42] and emotional factors [43][44][45]. The relationship between stress, psychiatric problems and the WAI is complex and probably cyclical: according to the Stockholm County longitudinal study, after 4 years, compared to their colleagues, workers with a low WAI had an almost two-fold rate of distress [46].…”
Section: Discussionmentioning
confidence: 99%
“…Noise is the most common physical occupational factor across the world and is the main source of physical injuries that are caused by work [1]. Numerous studies have shown that harmful factors in the workplace such as noise, vibration, and shift work and so on have detrimental effects on workers' health [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%